2011
DOI: 10.5694/mja11.10451
|View full text |Cite
|
Sign up to set email alerts
|

Implementing electronic medication management at an Australian teaching hospital

Abstract: We describe the implementation of an electronic medication management system (eMMS) in an Australian teaching hospital, to inform future similar exercises. The success of eMMS implementation depends on: a positive workplace culture (leadership, teamwork and clinician ownership); acceptance of the major impact on work practices by all staff; timely system response to user feedback; training and support for clinicians; a usable system; adequate decision support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…Our qualitative studies at the study sites revealed clinicians' greatest concern regarding the introduction of e-prescribing systems was the associated work practice changes [46], and qualitative and observational studies may best identify the nature of these changes. Experience has shown that embedding systems into everyday practice is a long-term project [13]. Importantly, the results highlight the need to continually monitor and refine the design of these systems to increase their capacity to improve both the safety and appropriateness of medication use in hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our qualitative studies at the study sites revealed clinicians' greatest concern regarding the introduction of e-prescribing systems was the associated work practice changes [46], and qualitative and observational studies may best identify the nature of these changes. Experience has shown that embedding systems into everyday practice is a long-term project [13]. Importantly, the results highlight the need to continually monitor and refine the design of these systems to increase their capacity to improve both the safety and appropriateness of medication use in hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…There is little work comparing commercial systems or the interactions between system design and error rates and types, despite increasing concerns regarding new errors associated with their use [8],[10],[11]. Implementation of these organisation-wide clinical information systems is complex [12],[13] with a multitude of work process and cultural factors [14][16], which affect system adoption and use, driving both intended and unintended outcomes [10],[11],[17],[18].…”
Section: Introductionmentioning
confidence: 99%
“…Medication safety experts have seen eMM as a solution to medication safety problems for the 21st century [11]. However, the variety of eMM systems available attest to the fact that after two decades, there is not yet a perfect solution [23]. If electronic medication management is integrated effectively within existing systems, optimal prescribing, documentation and communication should occur, leading to seamless transitions between hospital and the home.…”
Section: Pharmacy Based Medication Safety Programs Preparing For Tmentioning
confidence: 99%
“…In the Australian context, this has led to long lead times for adoption and post-go-live maturity 8. In Western Sydney, the experience of implementing EMR prior to EMM had ingrained a culture of digitisation and electronic documentation.…”
Section: Introductionmentioning
confidence: 99%